Dominant inflammatory profile of the placenta in a preterm labor mouse model. (2nd June 2020) - Yi, Xiaochun; Liu, Huixiang; Ou, Yuhua; Liu, Meilan; Zhu, Liqiong; Chen, Hui; Zhang, Jianping
Abstract: Objective: Despite a growing association between inflammation and preterm labor, the underlying mechanisms explaining the development of preterm labor after infection are still poorly understood. Here, we use RNA-sequencing to characterize the transcriptome changes of placenta tissue in a preterm labor mouse model. Materials and methods: On day 15.5 of gestation, BALB/c mice received intrauterine injection of LPS to mimic preterm labor. A comprehensive catalog of genes was obtained using RNA-sequences and followed by bioinformatics analysis. The NOD-like receptor signaling pathway (Nod2, Cxcl1, Cxcl2, and IL-1β) and two downregulated genes (Ctsg and Snca) were selected for validating the results using qPCR analysis. Results: We identified 155 differentially expressed genes (DEGs), 84 biological processes and 45 pathways in the placenta using RNA-seq. Fifty-four biological processes could be categorized as immune-related processes and 33 pathways were mainly related to immune disease and infections. All genes were consistent between the RNA-seq and qPCR analyses. Conclusions: The dominant role for inflammatory biological processes and pathways in placenta can lead to preterm labor.